Xpert MTB/RIF on Stool Is Useful for the Rapid Diagnosis of Tuberculosis in Young Children With Severe Pulmonary Disease - Walters, Elisabetta; van der Zalm, Marieke Magrieta; Palmer, Megan; Bosch, Corné; Demers, Anne-Marie; Draper, Heather; Goussard, Pierre; Schaaf, Hendrik Simon; Friedrich, Sven Olaf; Whitelaw, Andrew; Warren, Robin; Gie, Robert P; et al. (The Pediatric infectious disease journal, 2017)
Tuberculosis (TB) continues to result in high morbidity and mortality in children from resource-limited settings. Diagnostic challenges, including resource-intense sputum collection methods and insensitive diagnostic tests, contribute to diagnostic delay and poor outcomes in children. We evaluated the diagnostic utility of stool Xpert MTB/RIF (Xpert) compared with bacteriologic confirmation (combination of Xpert and culture of respiratory samples). In a hospital-based study in Cape Town, South Africa, we enrolled children younger than 13 years of age with suspected pulmonary TB from April 2012 to August 2015. Standard clinical investigations included tuberculin skin test, chest radiograph and HIV testing. Respiratory samples for smear microscopy, Xpert and liquid culture included gastric aspirates, induced sputum, nasopharyngeal aspirates and expectorated sputum. One stool sample per child was collected and tested using Xpert. Of 379 children enrolled (median age, 15.9 months, 13.7% HIV infected), 73 (19.3%) had bacteriologically confirmed TB. The sensitivity and specificity of stool Xpert versus overall bacteriologic confirmation were 31.9% [95% confidence interval (CI): 21.84%-44.50%] and 99.7% (95% CI: 98.2%-100%), respectively. A total of 23/51 (45.1%) children with bacteriologically confirmed TB with severe disease were stool Xpert positive. Cavities on chest radiograph were associated with Xpert stool positivity regardless of age and other relevant factors [odds ratios (OR) 7.05; 95% CI: 2.16-22.98; P = 0.001]. Stool Xpert can rapidly confirm TB in children who present with radiologic findings suggestive of severe TB. In resource-limited settings where children frequently present with advanced disease, Xpert on stool samples could improve access to rapid diagnostic confirmation and appropriate treatment.